Detailed MR Imaging Anatomy of the Abducent Nerve: Evagination of CSF into Dorello Canal - Ono, Kenichiro (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: The abducent nerve is difficult to identify reliably and consistently with conventional radiologic techniques. In this study, a 3D fast asymmetrical spin-echo MR imaging technique was used to obtain detailed images of the abducent nerve in normal volunteers. METHODS: The 3D fast asymmetrical spin-echo MR protocol was used to image the abducent nerves in 24 normal volunteers by using a 1-mm section thickness in the tilted axial and parasagittal planes. The microanatomy of the abducent nerve within Dorello’s canal was also demonstrated in a cadaver study. RESULTS: In 24 normal volunteers, the anatomy of 47 abducent nerves was clearly depicted on MR images. The length of the cisternal segment of the abducent nerve, extending from the brain stem to its dural foramina, ranged from 6.7 to 19.6 mm (mean, 13.1 mm). The abducent nerves were at an angle of 5 to 90 degrees (mean, 24.5 degrees) to the clivus. CSF evagination was detected in the region of Dorello’s canal in 36 (77%) of 47 abducent nerves. The length of CSF evagination varied: 0.9 mm in five nerves, 1.0 to 1.9 mm in 18 nerves, 2.0 to 2.9 mm in eight nerves, and 3.0 mm or more in five nerves. Histologic examination of serial sections of the abducent nerve revealed that the petroclival segment of the nerve was covered by an envelope composed of an arachnoid cell layer. CONCLUSION: The course of the abducent nerve was reliably identified using the 3D fast asymmetrical spin-echo MR protocol and a histologically proven arachnoid envelope around the petroclival segment of the nerve was shown as CSF evagination into Dorello’s canal by MR imaging.